'High entropy alloys'—'semi-impossible' regular solid solutions?. (July 2015) - Tomilin, I. A.; Kaloshkin, S. D.
Abstract : The article discusses the concept of high entropy alloys, introduced over the last decade and offering a methodology for development of new materials with enhanced properties, as well as the classification of such materials into a special category of multicomponent solutions. It is argued that the efficiency of this approach and applicability of the theory of regular solutions, on which the concept of high entropy alloys is based to materials science of multicomponent systems, are strongly exaggerated. The idea of random distribution of atoms in high entropy alloy structure is appropriate in fact only for ideal solid solutions, and there is no advantage in using it to understand the regularities of formation of complex alloys with special properties.